Sistema nacional de inversión pública y los proyectos de inversión en la municipalidad distrital de Huaso: 2011- 2016 - Ramos Valverde, Edi Hivan (2019)
In this work the work experience is reported in the Sub Programming and Investment Management of the District Municipality of Huaso. The case of the Public Investment Project is presented: “Installation and improvement of the drinking water and latrines service in the hamlets of El Progreso, Idabungo, Huaynas, Casapamba, La Vega, Intillacta and Parasive, district of Huaso - Julcán - La Libertad”, Which has the SNIP code in the Project Bank of the Ministry of Economy and Finance No. 248153, which is the main activity that was carried out as an evaluator of the PIP, in this specific area. The case of the project consists of supplying drinking water to all the families of the intervention hamlets, as well as providing them with the service of basic sanitation units (UBS), these being understood as latrines with hydraulic drag which has a storage tank, tank biodigester, toilet, shower and laundry, thus reducing gastrointestinal, parasitic and dermal diseases, improving the quality of life of the population.